An optimized poly(vinylidene fluoride-hexafluoropropylene)–NaI gel polymer electrolyte and its application in natural dye sensitized solar cells - Mohd. Noor, Mazni; Buraidah, M.H.; Careem, M.A.; Majid, S.R.; Arof, A.K. (Elsevier Ltd, 2014)
Gel type polymer electrolytes with PVDF-HFP as polymer host, NaI salt and EC/PC as plasticizers have been prepared and optimized for use in a dye sensitized solar cell (DSSC). The polymer electrolyte containing 48 wt. % (PVDF-HFP)–32 wt. % NaI–20 wt. % (EC/PC) exhibits the highest room temperature conductivity of 1.53 × 10−4 S cm−1. This electrolyte has been used in the fabrication of a DSSC with the configuration FTO/TiO2/natural dye/electrolyte/Pt/FTO. The natural dyes used anthocyanin and chlorophyll were solvent extracted from black-rice and pandanus amaryllifolius leaves respectively. UV-vis absorption spectra of anthocyanin, chlorophyll and the mixture of anthocyanin and chlorophyll in the volume ratio 1:1 were recorded. The anthocyanin shows an absorption peak at 532 nm. In the same region chlorophyll absorption shows a peak at 536 nm and also has a prominant peak at 665 nm. On mixing anthocyanin and chlorophyll two prominant peaks are observed at 536 and 665 nm. The DSSC containing the dye mixture exhibits the best performance with a short-circuit current density of 2.63 mA cm−2, open-circuit voltage of 0.47 V, fill factor of 0.58 and the highest photo-conversion efficiency of 0.72% under the illumination of 100 mW cm−2 white light. Under illumination of lower light intensity of 60 mW cm−2 and 30 mW cm−2, the fill factor enhanced from 0.58 to 0.59 and 0.60 and the photo-conversion efficiency increased from 0.72% to 1.11% and 1.85% respectively.